Clinical and pathogenetic prediction of the dynamics of the course of psychoses in epilepsy - S.G. Nosov; L.М. Yuryeva; T.Y. Shusterman; O.V. Nekrasova (Medičnì Perspektivi)
Transient epileptic psychoses in 30-40% of cases turn into psychotic states with a long, paroxysmal or chronic course. The objective of this article is to conduct a systematic analysis of modern literature sources to clarify the factors, clinical and pathogenetic patterns of transformation of transient (short-term) epileptic psychosis into psychotic states with prolonged and chronic course, as well as to identify pathogenetically oriented principles of treatment of such patients. The prognostic value of clinical and neurophysiological factors regarding increasing of the psychotic process duration has been noticed, clinical patterns of transformation of short-term psychosis into long-term (changes in the dynamics and structure of psychosis, features of the relationship with organic personality disorder and dementia in epilepsy, as well as epileptic seizures) have been shown. A number of important neurophysiological pathogenetic mechanisms of increasing the psychosis duration (growing cerebral hypofrontality, temporal localization and regular spread of the epileptic process) have been identified. Pathogenetically oriented principles of treatment tactics of patients with epileptic psychoses have been described and analyzed taking into account the revealed regularities of increasing of their duration.